2017
DOI: 10.3390/ijms18112283
|View full text |Cite
|
Sign up to set email alerts
|

Xanthine Oxidase Inhibitors for Improving Renal Function in Chronic Kidney Disease Patients: An Updated Systematic Review and Meta-Analysis

Abstract: Background: Accruing evidence suggests that Xanthine Oxidase inhibitors (XOis) may bring direct renal benefits, besides those related to their hypo-uricemic effect. We hence aimed at performing a systematic review of randomized controlled trials (RCTs) to verify if treatment with XOis may improve renal outcomes in individuals with chronic kidney disease (CKD). Methods: Ovid-MEDLINE, PubMed and CENTRAL databases were searched for RCTs comparing any XOi to standard therapy or placebo. The primary endpoint of int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 38 publications
1
22
0
2
Order By: Relevance
“…1 Furthermore, information for the effects of xanthine oxidase inhibitors on early kidney damage is sparse or lacking. 9 Febuxostat, a novel potent nonpurine-selective inhibitor of xanthine oxidase for oral use, is metabolized predominantly in the liver by glucuronidation, with only 1% to 6% of the dose being excreted unchanged through the kidneys. 10 Hence, decreased glomerular filtration rate (GFR) has little impact on the pharmacokinetic profile of febuxostat, 11 allowing its safe administration for patients with low GFRs.…”
mentioning
confidence: 99%
“…1 Furthermore, information for the effects of xanthine oxidase inhibitors on early kidney damage is sparse or lacking. 9 Febuxostat, a novel potent nonpurine-selective inhibitor of xanthine oxidase for oral use, is metabolized predominantly in the liver by glucuronidation, with only 1% to 6% of the dose being excreted unchanged through the kidneys. 10 Hence, decreased glomerular filtration rate (GFR) has little impact on the pharmacokinetic profile of febuxostat, 11 allowing its safe administration for patients with low GFRs.…”
mentioning
confidence: 99%
“…This is an unexpected finding, as many studies suggested that cancer risk would be increased in the CKD patients. [ 7 12 , 21 31 ] The further surprising finding was that our study showed a negative association between CKD and GC.…”
Section: Discussionmentioning
confidence: 53%
“…This hypothesis might explain the conflicting results reported in studies investigating the use of urate- lowering treatments in adults with established hypertension or chronic renal disease. Thus, at variance with these data, small pilot studies conducted in children and adolescents showed a reduction in blood pressure [ 63 , 64 ] and improvement in insulin sensitivity [ 99 , 100 ] and CKD [ 101 ] with the use of urate-lowering treatments. We believe further studies are needed before definitive conclusions can be drawn regarding the reversibility of the mechanisms sustaining the relationship between fructose, uric acid and all the metabolic dysregulations.…”
Section: Why Are These Pathogenetic Mechanisms Extraordinarily Impmentioning
confidence: 99%